The Leveson Inquiry: there's a bargain to be struck over media freedom and regulation - Brock, G (2012)
The Leveson Inquiry into the culture, practice, and ethics of the British press was triggered when the phone-hacking scandal’s full scale became clear in July 2011 and closed the News of the World. But the inquiry has gone much wider than that, hearing evidence about accuracy, fairness, privacy, regulation, and law. Much of the debate in and around the inquiry has focused narrowly on possible improvements to the much-criticized system of self-regulation for the press. This policy brief argues that a broader look at the relationship between the law and regulation would suggest that there is a bargain to be struck. A balanced outcome from the inquiry could both strengthen the legal defences for good journalism done in the public interest and create incentives for regulation which does not rely on statutory backing. Both the law and regulation must make more use of an effective public interest test.